Identification of a novel locus on chromosome 2q13, which predisposes to clinical vertebral fractures independently of bone density. Issue 3 (23rd November 2017) - Alonso, Nerea; Estrada, Karol; Albagha, Omar M E; Herrera, Lizbeth; Reppe, Sjur; Olstad, Ole K; Gautvik, Kaare M; Ryan, Niamh M; Evans, Kathryn L; Nielson, Carrie M; Hsu, Yi-Hsiang; Kiel, Douglas P; et al.
Abstract : Objectives: To identify genetic determinants of susceptibility to clinical vertebral fractures, which is an important complication of osteoporosis. Methods: Here we conduct a genome-wide association study in 1553 postmenopausal women with clinical vertebral fractures and 4340 controls, with a two-stage replication involving 1028 cases and 3762 controls. Potentially causal variants were identified using expression quantitative trait loci (eQTL) data from transiliac bone biopsies and bioinformatic studies. Results: A locus tagged by rs10190845 was identified on chromosome 2q13, which was significantly associated with clinical vertebral fracture (P=1.04×10 −9 ) with a large effect size (OR 1.74, 95% CI 1.06 to 2.6). Bioinformatic analysis of this locus identified several potentially functional SNPs that are associated with expression of the positional candidate genes TTL (tubulin tyrosine ligase) and SLC20A1 (solute carrier family 20 member 1). Three other suggestive loci were identified on chromosomes 1p31, 11q12 and 15q11. All these loci were novel and had not previously been associated with bone mineral density or clinical fractures. Conclusion: We have identified a novel genetic variant that is associated with clinical vertebral fractures by mechanisms that are independent of BMD. Further studies are now in progress to validate this association and evaluate the underlying mechanism.